Impact of Violence and Relationship Abuse on Grades of American Indian/Alaska Native Undergraduate College Students. Issue 23 (December 2018) - Patterson Silver Wolf, David A.; Perkins, Jacob; Van Zile-Tamsen, Carol; Butler-Barnes, Sheretta
Violence and relationship abuse are pervasive public health problems that have a range of negative effects, with exceptionally high prevalence among ethno–racial minority youth. This study assesses the prevalence of these types of violence among American Indian/Alaska Native (AI/AN) students and examines the impact of victimization on academic performance of AI/AN and non-AI/AN student populations using self-reported college health survey data. Results show that students who identified fully or partially as AI/AN reported markedly higher rates of all types of violence/abuse than did other students, and students who had experienced violence/abuse had lower grade point averages (GPAs) compared with those who had not. Recommendations for future research and direct practice with AI/AN students are discussed.